Optimization of Urban-Scale Sustainable Energy Strategies to Improve Citizens' Health - Adibhesami, Mohammad Anvar; Karimi, Hirou; Sharifi, Ayyoob; Sepehri, Borhan; Bazazzadeh, Hassan; Berardi, Umberto (Mdpi, 2023)
Sustainable energy strategies have been a critical subject for sustainable development, especially in cities. Citizens, as an integral part of the urban environment, play a significant role in urban spaces, as does their health. An accurate understanding of citizens' mental, social, and physical health in urban settings is required to design and plan better cities. This study aims to assess the level of alignment with health factors in Mahabad, a major medium-sized city in Iran. Previous studies indicate that the built environment can influence health dimensions. Health factors depend to a great extent on how well the environment is formed and how it is put together. This research is a descriptive, analytical, cross-sectional study that analyzes the environment's psychological elements and physical and mental health factors of Mahabad's citizens. According to the Cochran model, 384 questionnaires were distributed among households. For data analysis, SPSS 12 and Arc GIS software were used. The main results of this research show that five factors, Environmental quality, Identity and social relationships, and Readability, have the most impact on the physical and mental health of citizens (respondents). These issues are much more pronounced in the downtown neighborhoods. This study showed that urban experts can understand different levels of public health by knowing the historical, social, cultural, and economic factors and characteristics. The result will help decision makers, city authorities, designers, and urban planners to be more informed about citizens' health and the ways to improve it.
Keywords: sustainable energy strategies; healthy urban design; public health; sustainable development